Information System Design for Local Tax Revenue Planning in Surabaya City - Ramadhan Jatmiko, Muhammad Ammarul; Utami, Ardhini Warih (Journal of Education Technology and Information System, 2025)
Surabaya has great potential for regional tax revenue, but the planning process remains manual, resulting in inaccurate data, delays, and lack of system integration. This study aims to design and develop an information system to support more accurate and efficient regional tax revenue planning. The method used is Rapid Application Development (RAD), an iterative approach based on user feedback. Data were collected through interviews, observations, and literature review. The system is web-based, developed using C# and ASP.NET Core. Key features include tax account management, revenue component input, and component-based planning evaluation. Implementation results show the system improves data accuracy, planning efficiency, and administrative transparency. It also helps Surabaya's Regional Revenue Agency monitor real-time revenue planning. This research contributes to strengthening local tax management and supports digital transformation in public services.